Antarctic bacterial haemoglobin and its role in the protection against nitrogen reactive species - Coppola D; Giordano D; Tinajero Trejo M; di Prisco G; Poole RK; Verde C.; ASCENZI, Paolo (Biochimica et Biophysica Acta (BBA) - Proteins and Proteomics, 2013)
In a cold and oxygen-rich environment such as Antarctica, mechanisms for the defence against reactive oxygen and nitrogen species are needed and represent important components in the evolutionary adaptations. In the Antarctic bacterium Pseudoalteromonas haloplanktis TAC125, the presence of multiple genes encoding 2/2 haemoglobins and a flavohaemoglobin strongly suggests that these proteins fulfil important physiological roles, perhaps associated to the peculiar features of the Antarctic habitat. In this work, the putative role of Ph-2/2HbO, encoded by the PSHAa0030 gene, was investigated by in vivo and in vitro experiments in order to highlight its involvement in NO detoxification mechanisms. The PSHAa0030 gene was cloned and then over-expressed in a flavohaemoglobin-deficient mutant of Escherichia coli, unable to metabolise NO, and the resulting strain was studied analysing its growth properties and oxygen uptake in the presence of NO. We here demonstrate that Ph-2/2HbO protects growth and cellular respiration of the heterologous host from the toxic effect of NO-donors. Unlike in Mycobacterium tuberculosis 2/2 HbN, the deletion of the N-terminal extension of Ph-2/2HbO does not seem to reduce the NO scavenging activity, showing that the N-terminal extension is not a requirement for efficient NO detoxification. Moreover, the ferric form of Ph-2/2HbO was shown to catalyse peroxynitrite isomerisation in vitro, confirming its potential role in the scavenging of reactive nitrogen species. This article is part of a Special Issue entitled: Oxygen Binding and Sensing Proteins